Cooperative Responses of Multiple Kinesins to Variable and Constant Loads - Jamison, D. Kenneth (American Society for Biochemistry and Molecular Biology, 2012)
Microtubule-dependent transport is most often driven by collections of kinesins and dyneins that function in either a concerted fashion or antagonistically. Several lines of evidence suggest that cargo transport may not be influenced appreciably by the combined action of multiple kinesins. Yet, as in previous optical trapping experiments, the forces imposed on cargos will vary spatially and temporally in cells depending on a number of local environmental factors, and the influence of these conditions has been largely overlooked. Here, we characterize the dynamics of structurally defined complexes containing multiple kinesins under the controlled loads of an optical force clamp. While demonstrating that there are generic kinetic barriers that restrict the ability of multiple kinesins to cooperate productively, the spatial and temporal properties of applied loads is found to play an important role in the collective dynamics of multiple motor systems. We propose this dependence has implications for intracellular transport processes, especially for bidirectional transport.